Robotically Assisted Pterygium Surgery: First Human Case. Issue 10 (October 2015) - Bourcier, Tristan; Chammas, Jimmy; Becmeur, Pierre-Henri; Danan, Jérémy; Sauer, Arnaud; Gaucher, David; Liverneaux, Philippe; Mutter, Didier
Abstract : Purpose: Little research has been done on robotic ocular microsurgery. This study aims to demonstrate the feasibility of pterygium surgery using a robotic surgical system. Methods: Robot-assisted pterygium surgery was performed on a 73-year-old patient with nasal and temporal pterygia using the DaVinci Si HD robotic Surgical System (Intuitive Surgical Inc). The Kenyon technique (excision coupled with a conjunctival autograft) was performed. Results: The DaVinci system provided appropriate dexterity to perform the different steps of surgery. The operative time was 60 minutes 30 seconds. There were no intraoperative complications and no need for conversion to conventional surgery. Postoperative follow-up was unremarkable. Conclusions: Robot-assisted pterygium removal is technically feasible using the DaVinci Si HD robotic Surgical System. We report the first human case of robot-assisted pterygium surgery. Clinical Trial Registration —URL:http://www.clinicaltrials.gov . Unique identifier: NCT02116062.